Christina Reid's Theatre of Memory and Identity Within and Beyond the Troubles - Tracie, Rachel (Springer International Publishing, 2018)
This book is a study of the plays, performances and writings of Christina Reid. It explores Reid's work through her own words, both in interviews and writings; through theoretical engagements in other disciplines, such as psychology and geography; and through responses to her plays in production. It is a compilation of sorts, gathering together interviews, critical material, unpublished works and theatrical reviews to reflect the breadth and depth of Reid's contribution to the theatrical culture of Northern Ireland, during the Troubles and beyond.